(untitled) (American Journal of Technology and Applied Sciences, 2024)
In children with rickets, significant changes in the composition of higher fatty acids have been identified. The depth of changes in the composition of higher fatty acids depended on the severity of the pathological process. The revealed violations of the composition of higher fatty acids were corrected using apricot oil and Aevit, the results of using corrective therapy with apricot oil and Aevit for the treatment of children with rickets are presented. The effectiveness of this method of treatment of children with rickets is shown.